Notice of an Artificial Cave in the Parish of Alvey, Inverness-shire (Proceedings of the Society of Antiquaries of Scotland, 1864)
Sir David Brewster gives a notice of an artificial cave uncovered near Kingussie. The notice is accompanied by an illustration of the cave.